An exploratory study on oil and gas contributions towards UN millennium development goals - Tengku Mahmood, Tengku Noraida (2017)
Oil and gas industry is a very sensitive industry with much criticism from society and key stakeholders on the impact of their operations from environmental degradation, human right misconduct and negative social development. However, the energy that they produce and supply is an important source for economic, human and social development.